Clinical characteristics and patient-reported outcomes in patients with inadequately controlled rheumatoid arthritis despite ongoing treatment. Issue 1 (17th March 2018) - Taylor, Peter C; Alten, Rieke; Gomez-Reino, Juan J; Caporali, Roberto; Bertin, Philippe; Sullivan, Emma; Wood, Robert; Piercy, James; Vasilescu, Radu; Spurden, Dean; Alvir, Jose; Tarallo, Miriam
Abstract : Background: Despite the wide array of treatments available for rheumatoid arthritis (RA), some patients continue to report unmet clinical needs. We investigated the extent of inadequate disease control in patients with RA. Methods: Data were drawn from the Adelphi 2014 RA Disease-Specific Program in France, Germany, Italy, Spain and the UK. Rheumatologists provided patient demographics, comorbidities, satisfaction with RA control and other clinical details. Patients reported their level of satisfaction and completed the EuroQoL 5-Dimensions Health Questionnaire and Work Productivity and Activity Impairment Questionnaire. Patients had been on their current therapy ≥3 months and had 28-joint disease activity scores (DAS28) reported. Adequately controlled (DAS28 ≤3.2) and inadequately controlled (DAS28 >3.2) patient cohorts were compared using univariate tests. Results: Of 1147 patients, 74% were women, the mean age was 52 years and the mean time since RA diagnosis was 7 years. Twenty-seven percent of patients had inadequately controlled RA, whereas 73% had adequately controlled RA. Inadequately controlled patients were more affected clinically versus adequately controlled patients; 69% vs 13% had moderate/severe RA, the current level of pain was 4.6 vs 2.3, and 67% vs 41% experienced flares, respectively (all p<0.0001). Inadequately controlled patients had higher rates of depression (16% vs 5%; p<0.0001), worse health state, greater work and activity impairment, and lower satisfaction rates among the patients and their physicians than the adequately controlled cohort. Conclusion: RA was insufficiently controlled in over a quarter of patients despite their current therapy and this had a negative impact on the patients.